Significance of Multiple Lymphocyte-to-C-Reactive Protein Ratios in Predicting Long-Term Major Cardiovascular Adverse Events in Emergency Percutaneous Coronary Intervention Patients with ST-Segment Elevation Myocardial Infarction - Ye J; Xu D; Yuan R; Cao S; Wang Z; Wang Y; Li C; Zong G (Dove Medical Press, 2024)
Jiangping Ye,1- 3 Dongxia Xu,1- 3 Rikang Yuan,1- 3 Shaoqing Cao,1- 3 Zhangyu Wang,1- 3 Yuqin Wang,1- 3 Chengsi Li,1- 3 Gangjun Zong1- 3 1Wuxi Clinical College of Anhui Medical University, Wuxi, Jiangsu, People's Republic of China; 2Anhui Medical University Fifth Clinical Medical College, Wuxi, Jiangsu, People's Republic of China; 3Department of Cardiology, The 904th Hospital of Joint Logistic Support Force of PLA, Wuxi, Jiangsu, People's Republic of ChinaCorrespondence: Gangjun Zong, Email zonggj@163.comAim: The high morbidity and mortality associated with ST-segment elevation myocardial infarction (STEMI) are an urgent concern. This study aimed to investigate the ratio of lymphocyte count to C-reactive protein ratio (LCR) in multiple measurements in the perioperative period, exploring dynamic changes as the best predictor of major adverse cardiovascular events (MACE) in STEMI patients.Methods: We enrolled 205 STEMI patients, conducting blood counts at admission, 24 hours post-percutaneous coronary intervention (PCI), and at discharge. Cox proportional risk models evaluated factors independently associated with STEMI prognosis. The receiver operating characteristic (ROC) curve and the De-Long test determined the best predictor. Kaplan-Meier analysis assessed the prognostic value of LCR for STEMI patients. Statistical differences and correlations between LCR at 24 hours post-PCI and cardiovascular disease risk factors were also analyzed.Results: Gensini score (HR, 1.015; 95% CI, 1.007- 1.022; P < 0.001), total stent length (HR, 1.015; 95% CI, 1.002- 1.029; P=0.025), lipoprotein (a) (HR, 1.001; 95% CI, 1.000- 1.002; P=0.043), LCR at admission (HR, 0.995; 95% CI, 0.989- 1.000; P=0.002), and LCR at 24 hours post-PCI (HR, 0.587; 95% CI, 0.486- 0.708; P < 0.001) were independent risk factors for long-term STEMI prognosis after PCI. LCR at admission (cut-off value, 2.252; 95% CI, 0.040- 0.768; P < 0.001) and LCR at 24 hours post-PCI (cut-off value, 2.252; 95% CI, 0.831- 0.924; P < 0.001) effectively predicted MACEs occurrence, with the latter exhibiting a superior predictive effect (P< 0.001). Kaplan-Meier analysis revealed that patients with LCR at admission ≤ 50.29 and LCR at 24 hours post-PCI ≤ 2.25 had significantly higher risks of developing MACEs (Log-rank P < 0.0001).Conclusion: LCR at 24 hours post-PCI may be a superior marker for long-term MACE prediction in STEMI patients, serving as the best predictor for distant MACE occurrence.Keywords: lymphocyte, C-reactive protein, major cardiovascular adverse events, percutaneous coronary intervention, ST-segment elevation myocardial infarction